Toll-like Receptors in Innate Immunity - Hadi, Najah R.; Shaker, Saad Rasool; Alharis, Nada R (Important Aspects of Toll-like Receptors: Signaling Pathways in Diseases, 2021)
Innate immunity is present in both vertebrates and invertebrates, raising the possibility that investigation of host defense mechanisms in model organisms prone to genetic analysis, such as the fruit fly Drosophila, may shed light on the nature of the elusive Pattern Recognition Receptors. The family of Toll-like receptors plays an essential role in the induction of the immune response. These receptors sense the presence of microbial ligands and activate the nuclear factor-_B transcription factor. The name of Toll-like receptors comes from the vernacular German Toll, meaning super or fantastic. Functional characterization of Toll-like receptors (TLRs) has established that innate immunity is a skillful system that detects invasion of microbial pathogens. Recognition of microbial components by TLRs initiates signal transduction pathways, which triggers expression of genes. These gene products control innate immune responses and further instruct development of antigen-specific acquired immunity.